MG-133 Development and launch of an expanded pan-ethnic carrier screening panel. (4th December 2015) - Birch, Ashley H; Cai, Guiqing; Cai, Xiaoqiang; Fedick, Anastasia; Elkhoury, Lama; McCarthy, Janelle; Delio, Maria; Zhang, Jinglan; Kornreich, Ruth; Edelmann, Lisa
Abstract : Background: Prenatal carrier screening has traditionally focused on well-defined ethnic groups with an increased chance of being a carrier for specific genetic diseases. However, many people are of mixed ethnicity or cannot accurately identify their full ethnic. With the ability to test for hundreds of diseases at one time, expanded carrier screening panels are an attractive option. Objectives: To build a comprehensive pan-ethnic carrier screening panel with a rapid turnaround time (TAT). Design/method: Following literature review, internal research, and physician input, a panel of 281 autosomal recessive and X-linked diseases were selected. Next generation sequencing (NGS) was performed using Agilent's SureSelect QXT target enrichment approach followed by Illumina HiSeq 2500 Rapid Run mode sequencing. Additional methodologies include MLPA, Asuragen CGG repeat analysis/Southern blotting, and Sequenom/Luminex genotyping assays to assay variants not amenable to NGS. Variant confirmation is performed simultaneously by genotyping, or subsequently by Sanger sequencing. Over 3, 700 recurrent pathogenic variants with a well-established relationship to disease phenotype are guaranteed to be sequenced at a depth of > 20X. Results: 524 validation samples were tested, including positive controls with various mutation types, and both prenatal and postnatal samples covering a variety of specimen types. A minimum average coverage of 240X was achieved, with > 20X coverage of 99% of bases. Conclusions: This panel can be customizable to order, including a high-frequency panel of 10 diseases, a Comprehensive Jewish panel of 96 diseases, and the full 281 gene panel. Automation can handle thousands of samples per month. TAT currently averages 8–10 days.